Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2000
DOI: 10.1055/s-2000-9687
|View full text |Cite
|
Sign up to set email alerts
|

Pacifier use and sleep position in 2 to 4 month old infants

Abstract: In clinically healthy 2-to-4-month-old babies, the use of a pacifier does not have major influence on the choice of sleep position and infant's propensity to spontaneously modify it during sleep.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 5 publications
(5 reference statements)
1
3
0
Order By: Relevance
“…Conversely, supine positioning, which was practised in 6% to 15% of infants prior to 1990, 16,17 has risen sharply to 55% to 65% in this decade, 19,20 consistent with the rate of 65% cited as the usual sleep position in this survey. These rates are similar to those recorded in the UK and Europe 21–23 . A slightly higher rate, 70%, was recorded in the USA in 2004, but prone sleeping rates were also higher, at 13% 24 .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Conversely, supine positioning, which was practised in 6% to 15% of infants prior to 1990, 16,17 has risen sharply to 55% to 65% in this decade, 19,20 consistent with the rate of 65% cited as the usual sleep position in this survey. These rates are similar to those recorded in the UK and Europe 21–23 . A slightly higher rate, 70%, was recorded in the USA in 2004, but prone sleeping rates were also higher, at 13% 24 .…”
Section: Discussionsupporting
confidence: 84%
“…These rates are similar to those recorded in the UK and Europe. [21][22][23] A slightly higher rate, 70%, was recorded in the USA in 2004, but prone sleeping rates were also higher, at 13%. 24 The difference is made up by the higher side and side-plus-back sleeping rates in New Zealand compared with lower rates for this position in the USA (32% in this study vs. 15% in the USA).…”
Section: Discussionmentioning
confidence: 92%
“…(1999) concluded that the use of pacifiers pacified the infants and, thus, caused them to fall asleep more easily (20). Kelmanson drew attention to the fact that pacifiers have been used for generations to soothe the crying infant (21). …”
Section: Discussionmentioning
confidence: 99%
“…Pollard et al(1999) concluded that pacifier use pacified the infants and thus caused them to fall asleep more easily. Kelmanson (2000) draw attention to the fact that pacifiers have been used for generations to soothe the crying infant.…”
Section: Advantages Of Pacifier Usementioning
confidence: 99%